Termoviskoz bulkFill kompozit rezin ile antagonist CAD CAM bloğunun aşınma direncinin incelenmesi - ŞENOL, AYŞE ASLI; KAHRAMANOĞLU, ERKUT; YILMAZ ATALI, PINAR; TÜRKMEN, CAFER (My University, 2022)
Molar incisor hypomineralization (MIH) is an enamel defect that develops in the molar and incisors as a result of exposure of ameloblast cells to various environmental and systemic factors during the maturation phase of amelogenesis, thus causing aesthetic concerns. In this case report microabrasion and home bleaching was planned for the treatment of MIH.A 17 years old female patient who referred to our clinic with the chief complaint of white lesions on maxillary incisor teeth, were examined clinical and radiographically In both the maxillary and mandibular arch, visible opacities were detected and microabrasion and home bleaching techniques were planned for the treatment of lesions. Before microabrasion application, Tooth Mousse Gel (GC) was applied on the lesions for two weeks. Shade selection was performed by spectraphotometer (Vita EasyShade V). Under the rubber dam isolation (maxillary-arch) and gingival barrier (mandibullary-arch) Opalustre (Ultradent) was applied in 3 consecutive cycles using OpalCups (Ultradent) according to manufacturer’s guidelines. Fluoride varnish (4% NAF, ProShield, President Dental) was applied for 4 minutes following the microabrasion. Home bleaching gel was applied for 5 weeks with custom made bleaching tray using 16% Carbamide Peroxide (Opalescence PF, Ultradent) Patient were recalled for 7,14,21,28 and 35 day. For the examination of the lesions and color of teeth.The using of ACP-CPP containing gel before the treatment, made a difference in the visibility of enamel hypomineralizations. The shades of incisor teeth which, was the patient’s complaint was B3 initially A2 after microbrasion and A1 after bleaching. The patient was satisfied with the treatment results.Application of remineralisation gel for two weeks, reduced the size of enamel hypomineralizations.The combined use of microabrasion and home bleaching is more effective in reducing lesions, eliminating aesthetic concerns and provided a more comfortable treatment process for the patient with MIH.
Keywords: Sağlık Bilimleri; Health Sciences; Klinik Tıp (MED); Clinical Medicine (MED)